The psychological ability to adopt recommended coping responses reduced infections during the COVID-19 pandemic - Lasse Hyldig Hansen; Frederik Jørgensen; Michael Bang Petersen (Proceedings of the National Academy of Sciences, 2026)
During the COVID-19 pandemic, a key question for researchers and authorities was to understand the psychological motivations that sustained public engagement in protective behavior such as physical distancing and hygienic protection. While feelings of threat were rampant during the pandemic, theories of health psychology have highlighted appraisals related to the ability to cope (e.g., the feeling of being able to adhere cost-effectively to government advice) and argued that coping appraisals are superior predictors of motivations to protect the self against risks. In this study, we conducted a massive population-based comparison of the association between, on the one hand, threat appraisals and coping appraisals and, on the other hand, protection against actual infection during the COVID-19 pandemic. We built a unique Danish data infrastructure that links surveys of ~8% of the adult population (N = 386,633) with the individual results of the 123 million COVID-19 tests performed during 22 mo of the COVID-19 pandemic. Controlling for a comprehensive range of sociodemographic measures and employing panel data to bolster internal validity, we observe that stronger coping appraisals are consistently associated with lower individual probability of COVID-19 infection risk. We find no consistent evidence of a similar association for threat appraisals. Threat appraisals rather seem to index individual feelings of infection exposure. As appeals to fear also have unintended negative consequences (including anxiety, fatigue, and stigmatization), the findings offer strong support for relying on coping-oriented public health policy and communication in future societal crises in the domain of health and beyond.